Intraosseous Lipoma of the Calvaria in the Early Stage Resembling Normal Fatty Marrow - Nagase, Shunsuke; Ogura, Kanako; Ashizawa, Karin; Sakaguchi, Asumi; Hotchi, Shiori; Hishii, Makoto; Fukunaga, Masaharu; Matsumoto, Toshiharu (Journal of Neurological Surgery Reports, 2022)
Intraosseous lipoma (IOL) is a benign bone tumor that usually arises from the lower limb and rarely arises from the skull. Radiological diagnosis of a typical case is not problematic due to its characteristic calcification and marginal sclerosis. Here, we report a case of calvarial IOL in the early stage lacking conventional radiopathological features. The patient is a 7-year-old girl who presented with a slow-growing protuberance on the vertex of the head. Computed tomography displayed a low-density mass without calcification that was continuous with the surrounding diploe. The mass was resected piece by piece for diagnostic and cosmetic reasons. Histologically, the specimen consisted of bony trabeculae and intertrabecular adipose tissue, which resembled normal fatty marrow. However, adipose tissue was considered neoplastic since it lacked hematopoietic elements. The final diagnosis of IOL was made by radiopathological correlation. This case suggests that IOL should be included in the differential diagnosis of diploic expansion, even if calcification is absent. The histology of an early-stage IOL resembles normal fatty marrow, but recognizing the absence of hematopoietic elements aids the diagnosis. Also, our literature review indicates that such cases are likely to be encountered in the calvaria than cranial base.
Keywords: early; intraosseous; lipoma; skull; calvaria; diploe